The firm. Organizational logic and criminal culture on a shifting terrain - Hobbs, Dick (The British journal of criminology, 2001)
This paper will seek to extend arguments made elsewhere concerning changes in criminal fraternities (Hobbs 1995, 1997a), by focusing upon the connections between criminal culture and the specific political economy of a locale. It argues that within serious crime networks, tendencies found in the organization of legitimate labour are reflected (Hobbs 1997a, Ruggiero 1995), and that as trade within and between criminal coalitions involves the generation and nurturing of local interests, one of the primary structures upon which organized urban crime is based, is the traditional neighbourhood family firm